Calculation of the Ettingshausen Coefficient in a Rectangular Quantum Wire with an Infinite Potential in the Presence of an Electromagnetic Wave (the Electron - Optical Phonon Interaction) - Hưng, Trần Hải; Quang, Doan Minh; Vi Ba, Cao Thi; Bau, Nguyen Quang (VNU Journal of Science: Mathematics - Physics, 2017)
The Ettingshausen coefficient (EC) in  a Rectangular quantum wire with an infinite potential (RQWIP)in the presence of an Electromagnetic wave (EMW) is calculated by using a quantum kinetic equation for electrons. Considering the case of the electron - optical phonon interaction, we have found the expressions of the kinetic tensors . From the kinetic tensors, we have also obtained the analytical expression of the EC in the RQWIP in the presence of EMW as function of the frequency and the intensity of the EMW, of the temperature of system, of the magnetic field  and of the characteristic parameters of RQWIP. The theoretical results for the EC are numerically evaluated, plotted and discussed for a specific RQWIP GaAs/GaAsAL. We also compared received EC with those for normal bulk semiconductors and quamtum wells to show the difference. The Ettingshausen effect in  a RQWIP in the presence of an EMW is newly developed.